Keruntuhan Progresif Gedung Beraturan Sistem Ganda - Fazrian, Dhika; Djauhari, Zulfikar; Ridwan, Ridwan (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
This research aimed to examine the progressive collapse of dual system building structures due to the loss of one or more structural elements that lead to successive collapse of other elements. Three cases of building structures were analysed in this study using finite element software. Several columns on the first floor of the structure was removed and then the analysis was conducted to each structure until the progressive collapse existed. The nonlinear statics analysis was used to examine the location of the critical column while the linear statics analysis was carried out to find the demand capacity ratio, the bending moment ratio and robustness indicator as suggested by GSA 2003 and SNI 2847-2013. The results showed that the structure denoted in case 1 and case 2 that was loaded comply with GSA 2003 experienced the progressive collapse. On the other hand this phenomenon did not appear on the structure that was loaded in accordance with SNI 2847-2013. Furthermore, there was an increase in the bending moment capacity of the column/beam on all cases that were loaded comply with SNI 2847-2013 and GSA 2003. Robustness indicator is almost equal one with the type of progressive collapse is pancake collapse type.Keywords : Progressive Collapse, Demand Capcaity Ratio, Bending Moment Ratio And Robustness Indicator.